2011
DOI: 10.1111/j.1420-9101.2011.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic variation for thermal performance curves within and among natural populations ofDrosophila serrata

Abstract: Thermal performance curves (TPCs) provide a powerful framework for studying the evolution of continuous reaction norms and for testing hypotheses of thermal adaptation. Although featured heavily in comparative studies, the framework has been comparatively underutilized for quantitative genetic tests of thermal adaptation. We assayed the distribution of genetic (co)variance for TPC (locomotor activity) within and among three natural populations of Drosophila serrata and performed replicated tests of two hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
85
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 71 publications
13
85
3
Order By: Relevance
“…The importance of an organism's locomotor activity in relation to stressful temperatures has also been addressed, and it has been suggested that high locomotor capacity in stressful environments is an indicator of an organisms ability to escape stressful conditions (Feder et al 2010; Kjaersgaard et al 2010). These observations are in agreement with the fact that locomotor activity in Drosophila is a highly dynamic trait that differs between populations (Gibert et al 2001; Latimer et al 2011). …”
Section: Introductionsupporting
confidence: 90%
“…The importance of an organism's locomotor activity in relation to stressful temperatures has also been addressed, and it has been suggested that high locomotor capacity in stressful environments is an indicator of an organisms ability to escape stressful conditions (Feder et al 2010; Kjaersgaard et al 2010). These observations are in agreement with the fact that locomotor activity in Drosophila is a highly dynamic trait that differs between populations (Gibert et al 2001; Latimer et al 2011). …”
Section: Introductionsupporting
confidence: 90%
“…From a behavioural perspective, for example at temperatures where the likelihood of encountering food is high, animals may increase their activity levels to maximise their net energy intake (Speakman 1986) or alternatively they may become less active, perhaps because predators could also be more prevalent (Anholt et al 2000; see also Werner and Anholt 1993). At excessive temperatures they may increase activity rates (Latimer et al 2011), perhaps in an attempt to seek out more favourable microclimates, or in contrast they may enter an inactive state of aestivation (Rees and Hand 1990). From a physiological perspective, there is a direct effect of temperature on the biochemical reactions involved in locomotion.…”
Section: Discussionmentioning
confidence: 98%
“…Of the few studies published on the relationship between activity levels and temperature, most are qualitative (e.g. Tomlinson and Phillips 2012); only rarely do papers present quantified relationships between voluntary activity and temperature (see also Biro et al 2010;Gannon et al 2014;Halcrow and Boyd 1967;Latimer et al 2011;Lighton and Duncan 2002;Morgan 1984Morgan , 1987Van Donk and De Wilde 1981). While several papers have included activity measures in MR-temperature experiments, these studies have typically been interested only in the presence or absence of activity, focussing on the time-point that activity ceases during temperature ramping protocols (Folk et al 2007;Lighton 2007;Lighton and Turner 2004;Stevens et al 2010).…”
mentioning
confidence: 97%
“…At present, only one draft genome assembly ( D. kikkawai ) is available (Chen et al 2014) from this species-rich subgroup. D. serrata has a broad geographical distribution, ranging from Papua New Guinea to south eastern Australia and has emerged as a powerful model for addressing evolutionary questions such as the evolution of species borders (Blows and Hoffman 1993; Hallas et al 2002; Magiafoglou et al 2002) and climate adaptation (Frentiu and Chenoweth 2010; Latimer et al 2011; Kellermann et al 2009). The species has also been used to investigate sexual selection (Hine et al 2002; Gosden and Chenoweth 2011; Frentiu and Chenoweth 2008; Chenoweth et al 2015), male mate choice (Chenoweth and Blows 2003; Chenoweth et al 2007), mate recognition (Higgie et al 2000), sexual dimorphism (Chenoweth et al 2008; Yassin et al 2016), sexual conflict (Delcourt et al 2009), and indirect genetic effects (Chenoweth et al 2010b).…”
mentioning
confidence: 99%